Protective Role of Propolis against Iron Overload Induced Genotoxicity and Oxidant/Antioxidant Status - Mjida A.J. Al-Qayim (Journal of Global Pharma Technology, 2016)
The current study designed to investigate the protecting role of propolis in DNA damage and oxidaant / antioxidant imbalance caused by iron overload. 24 adult male wister rats divided in to 3 equal groups and handled as following: 1st group(C) as control, 2nd group, IO) group IP iron dextran 100mg/ kg BW each 72 hr. 3rd (IOP) given IP iron dextran 100mg/ kg BW each72 hr. and orally Propolis crude extract (50 mg /kg body weight) daily for two months. Results revealed that administered rats with propolis showed enhancement in oxidant/anti-oxidant indicators, categorized by raise of GSH, and MDA reduction on the contrast with IO group. Propolis adiminstration to IO rats decreased the DNA damage and fragmentation. Conclusion, the present results are established for the first time a new role for the Propolis, in counter and reduce the iron overload harmful effects on DNA mainly via modulation of oxidant status in IO.